Fixed-to-mobile broadband substitution in South Africa. - Moroeng, Letlhogonolo Hendrick. (My University, 2012)
Broadband is an important technology for development. Research has proven that development is directly linked to high speed internet. Over the past few years mobile broadband has overtaken fixed-line broadband as a primary connection for many households. The purpose of this exploratory study was to investigate how pricing and quality of service have either encouraged or inhibited fixed-to-mobile broadband in South Africa, and research if there are any other factors affecting broadband growth. The study, conducted in a predominantly middle-income neighbourhood, found that there is a trend towards fixed-to-mobile broadband substitution in South Africa.
Keywords: Broadband; Mobile communication systems; South Africa